Auxetic yarn : fundamentals, influencing parameters, application areas and challenges - Khan, Md. Khalilur Rahman (Array, 2021)
The mechanical behaviour of auxetic materials and structures is the most distinctive characteristic, which differs from that of conventional engineering materials due to the negative Poisson"s ratio. Auxetic materials have the fascinating feature of widening when stretched and contracting when compressed. In recent times, the research of auxetic materials based on textile structures has received a lot of interest. Auxetic effect development at the yarn phase is a new and exciting field of study. Many researchers already developed different types of auxetic yarns, such as the helical auxetic yarn, the plied auxetic yarn, the semi-auxetic yarn etc. The helical auxetic yarn (HAY) is the most commonly mentioned auxetic yarn. It is made up of a rigid wrap and an elastic core yarn. However, it is interesting that auxetic yarns can be produced from conventional non-auxetic fibres through the conventional spinning system as well. The helical auxetic yarn is a new type of yarn with a wide variety of possible applications. Moreover, pore-opening characteristics of auxetic yarns make it a potential candidate in the fields of technical textiles, such as medical textiles, filter application, protective textiles etc. Fabrication of auxetic textiles by utilizing auxetic yarns through simple weaving and knitting technology opens the door to new applications. The aim of this paper is to address the fundamentals of auxetic yarns, such as structure, shortcomings, production techniques, as well as the influencing process parameters. From various research works, it is evident that the wrap helical angle, the core/wrap diameter ratio, and the initial moduli of wrap component are the most vital processing parameters during the production of auxetic yarns. Finally, some potential application areas and challenges of auxetic yarns are also addressed briefly in this paper.